Peran Humas Pemerintah Dalam Pemasaran #ViralkanKabarBaik Melalui Media Massa - Wahyudin, Uud; Purwningwulan, Melly Maulin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2018)
The purpose of government public relations activities is to build a good image for the institution. Toachieve its objectives, a mutually beneficial relationship is needed between PR and the mass media.This paper analyzes in depth the urgency of mass media in campaigning for #ViralkanKabarBaik asone of the government's public relations marketing media. The theory used is the media ecologicaltheory which focuses on many types of media and views media as an environment. The conclusion isthat #ViralkanKabarBaik fosters public confidence in the government. It is expected that publicrelations practitioners are more proactive in reporting positive things using varied media.